2019
DOI: 10.1136/bjophthalmol-2019-314804
|View full text |Cite
|
Sign up to set email alerts
|

Glaucoma following cataract surgery in the first 2 years of life: frequency, risk factors and outcomes from IoLunder2

Abstract: BackgroundWe investigated glaucoma related adverse events, predictors and impact at 5 years following surgery in the IoLunder2 cohortMethodsPopulation based observational cohort study of children undergoing cataract surgery aged 2 years or under between January 2009 and December 2010. Glaucoma was defined using internationally accepted taxonomies based on the consequences of elevated intraocular pressure (IOP). Glaucoma related adverse events were any involving elevated IOP. Multivariable analysis was undertak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
86
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(94 citation statements)
references
References 27 publications
6
86
2
Order By: Relevance
“…Treatment Study Registry (TAPS) and the IoLunder2 cohort, demonstrating that GRAE is a common complication threatening visual prognosis after cataract surgery in infants and young children, 3,[23][24][25] with incidence increasing gradually over the postoperative interval. The Infant Aphakia Treatment Study (IATS) reported that the incidence of GRAE in children aged one to six months at the time of cataract extraction rose from 12% at 1 year to 40% at 10 years after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment Study Registry (TAPS) and the IoLunder2 cohort, demonstrating that GRAE is a common complication threatening visual prognosis after cataract surgery in infants and young children, 3,[23][24][25] with incidence increasing gradually over the postoperative interval. The Infant Aphakia Treatment Study (IATS) reported that the incidence of GRAE in children aged one to six months at the time of cataract extraction rose from 12% at 1 year to 40% at 10 years after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Of these potentially relevant articles, 176 publications were excluded for various reasons, and 33 publications met the inclusion criteria and were included in this report. These comprised 3 RCTs [44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61] and 15 nonrandomized studies, [62][63][64][65][66][67][68][69][70][71][72][73][74][75][76] relevant to research questions 1, 2, 3, and 4. No economic evaluations relevant to research questions 5 and 6 were identified. There were 16 clinical publications and 1 methods publication (which was not included in the overall count) 77 that reported on the same RCT -the Infant Aphakia Treatment Study (IATS).…”
Section: Quantity Of Research Availablementioning
confidence: 99%
“…Several studies have shown that the younger the age at the time of surgery the higher the risk for secondary glaucoma. 4 6…”
Section: Introductionmentioning
confidence: 99%